Green building with concrete : sustainable design and construction - Sabnis, Gajanan M. (Boca Raton, FL : CRC Press, 2012)
'Packed with case studies highlighting construction companies that regularly recycle between 70% and 95% of concrete from their waste streams, this book presents practical, up-to-date information about concrete's history in the green building movement, state of the art methodologies, and current best practices. Using the USGBC LEED (Leadership in Energy and Environmental Design) green building assessment standard, the book covers site, energy, water, materials, indoor environmental quality, construction, and demolition waste protocols and provides information on tracking the LEED requirements to assure timely building certification. It also addresses non-LEED issues, such as flood and fire protection benefits'--
'Providing the most recent information about concrete's history in the green building movement, state-of-the-art methodologies and best practices, this book may be considered a textbook for university courses and industry education; a handbook to help building owners obtain green certification; a reference for industry professionals seeking an overview of the subject of concrete and green buildings; and as a guide to professionals in the building materials/products industries. The concept of green buildings is in the process of emerging from a decade long effort to define itself, and this book offers an overview of all of the available information'--
Includes bibliographical references and index.
Keywords: Concrete construction; Sustainable construction; Concrete -- Recycling